Toward Advanced Ionic Liquids. Polar, Enzyme-friendly Solvents for Biocatalysis - Gorke, Johnathan, University of Minnesota, Minneapolis, MN, USA; Srienc, Friedrich, University of Minnesota, Minneapolis, MN, USA; Kazlauskas, Romas, University of Minnesota, Minneapolis, MN, USA (Biotechnology and bioprocess engineering, 2010)
Ionic liquids, also called molten salt, are mixtures of cations and anions that melt below 100℃. Typical ionic liquids are dialkylimidazolium cations with weakly coordinating anions such as (MeOSO₃) or (PF∧6). Advanced ionic liquids such as choline citrate have biodegradable, less expensive, and less toxic anions and cations. Deep eutectic solvents are also included in the advanced ionic liquids. Deep eutectic solvents are mixtures of salts such as choline chloride and uncharged hydrogen bond donors such as urea, oxalic acid, or glycerol. For example, a mixture of choline chloride and urea in 1:2 molar ratio liquefies to form a deep eutectic solvent. Their properties are similar to those of ionic liquids. Water-miscible ionic liquids as cosolvents with water enhance the solubility of substrates or products. Although traditional water-miscible organic solvents also enhance solubility, they often inactivate enzymes, while ionic liquids do not. The enhanced solubility of substrates can increase the rate of reaction and often increases the regio- or enantioselectivity. Ionic liquids can also be solvents for non-aqueous reactions. In these cases, they are especially suited to dissolve polar substrates. Polar organic solvent alternatives inactivate enzymes, but ionic liquids do not even when they have similar polarities. Besides their solubility properties, ionic liquids and deep eutectic solvents may be greener than organic solvents because ionic liquids are nonvolatile, and can be made from nontoxic components. This review covers selected examples of enzyme catalyzed reaction in ionic liquids that demonstrate their advantages and unique properties, and point out opportunities for new applications. Most examples involve hydrolases, but oxidoreductases and even whole cell reactions have been reported in ionic liquids.